Political Science of Religion: Theorising the Political Role of Religion - Potz, Maciej (Springer eBooks Political Science and International Studies, 2020)
PART I. Reclaiming Religion for Political Science -- Chapter 1 Introduction: Why we need political science of religion -- Chapter 2 Political Science of Religion: Demarcating the field -- PART II. Theocracies -- Chapter 3 Religious Legitimation of Power and the Concept of Theocracy -- Chapter 4 Theocracies as Political Systems -- PART III. Religion in Democracies -- Chapter 5 Here to Stay: The role of religion in contemporary politics -- Chapter 6 Veto Players and Stakeholders: Religion in Polish and American politics